Assessment of Intramuscular Verapamil as Pharmacological Countermeasure in a Rat Model of Organophosphate DFP-induced Status Epilepticus - Yam Nath Paudel; Robert E. Blair; Elisa Hawkins; Matthew S. Halquist; Melissa Morgan; Jason Funderburk; Daniel Calvano; Jennifer Koblinski; Hope Richard; Laxmikant S. Deshpande (Neurotoxicity Research, 2025)
Lethal organophosphate (OP) exposure leads to status epilepticus (SE), which, despite standard-of-care (SOC) therapy, is associated with acute mortality and long-term morbidities. Neuronal injury and inflammation are reported following OP-SE, and drugs targeted at these processes have produced beneficial outcomes. Verapamil (VPM) is a calcium-channel blocker used as an antihypertensive drug and has been shown to exhibit neuroprotective and anti-inflammatory actions in experimental models of CNS injuries. Here, we investigated the feasibility of an adjunctive intramuscular (i.m.) VPM therapy in OP Diisopropyl Fluorophosphate (DFP)-induced SE. We also investigated the safety and toxicity of i.m. VPM and compared its pharmacokinetic (PK) profile to oral (p.o.) administration. Rats were injected with DFP (4 mg/kg, s.c.). One minute later, SOC treatment consisting of atropine (0.5 mg/kg, i.m.) and pralidoxime chloride (2-PAM; 25 mg/kg, i.m.) were administered, and at 1-hour post-SE, midazolam (1.78 mg/kg, i.m.) was given. Rats that met the behavioral SE severity criteria (Racine 4–5) were randomized into two treatment groups: those receiving saline (SAL) or VPM (10 mg/kg, i.m. bid , 3 days). Histological analysis was conducted to assess neuronal injury and injection-site pathology. In a separate group of rats, PK studies were conducted on blood and brain homogenates treated once with saline or VPM (10 mg/kg, p.o. or i.m.). Our data demonstrated that following DFP-SE, i.m. VPM achieved higher blood and brain levels and exhibited a favorable PK profile compared to p.o. route. VPM therapy did not cause significant muscle pathology and produced a robust neuroprotective response. Neuroinflammatory markers and long-term behavioral outcomes were not included in this study. Our studies provide evidence that the i.m. route is an effective method for delivering VPM following SE, producing significant neuroprotective outcomes compared to treatment with the standard-of-care alone in OP-SE.

Genome-wide analysis of hepatic DNA methylation reveals impact of epigenetic aging on xenobiotic metabolism and transport genes in an aged mouse model - Sara Abudahab; Mohamad M. Kronfol; Mikhail G. Dozmorov; Thomas Campbell; Fay M. Jahr; Jasmine Nguyen; Ola AlAzzeh; Dalia Y. Al Saeedy; Ashley Victor; Sera Lee; Shravani Malay; Dana M. Lapato; et al. (GeroScience, 2024)
Hepatic xenobiotic metabolism and transport decline with age, while intact xenobiotic metabolism is associated with longevity. However, few studies have examined the genome-wide impact of epigenetic aging on these processes. We used reduced representation bisulfite sequencing (RRBS) to map DNA methylation changes in liver DNA from mice ages 4 and 24 months. We identified several thousand age-associated differentially methylated sites (a-DMS), many of which overlapped genes encoding Phase I and Phase II drug metabolizing enzymes, in addition to ABC and SLC classes of transporters. Notable genes harboring a-DMS were Cyp1a2 , Cyp2d9 , and Abcc2 that encode orthologs of the human drug metabolizing enzymes CYP1A2 and CYP2D6, and the multidrug resistance protein 2 (MRP2) transporter. Cyp2d9 hypermethylation with age was significantly associated with reduced gene expression, while Abcc2 expression was unchanged with age. Cyp1a2 lost methylation with age while, counterintuitively, its expression also reduced with age. We hypothesized that age-related dysregulation of the hepatic transcriptional machinery caused down-regulation of genes despite age-related hypomethylation. Bioinformatic analysis of hypomethylated a-DMS in our sample found them to be highly enriched for hepatic nuclear factor 4 alpha (HNF4α) binding sites. HNF4α promotes Cyp1a2 expression and is downregulated with age, which could explain the reduction in Cyp1a2 expression. Overall, our study supports the broad impact of epigenetic aging on xenobiotic metabolism and transport. Future work should evaluate the interplay between hepatic nuclear receptor function and epigenetic aging. These results may have implications for studies of longevity and healthy aging.

Quantitative Determination of (R)-3-Hydroxybutyl (R)-3-Hydroxybutyrate (Ketone Ester) and Its Metabolites Beta-hydroxybutyrate, 1-3-Butanediol, and Acetoacetate in Human Plasma Using LC-MS - Nimishraj Panse; Matthew Halquist; Phillip M. Gerk (AAPS PharmSciTech, 2023)

Effects of device settings and e-liquid characteristics on mouth-throat losses of nicotine delivered with electronic nicotine delivery systems (ENDS) - Sana Hosseini; Vinit Gholap; Matthew S. Halquist; Laleh Golshahi (Journal of Aerosol Science, 2023)

Impact of Membranes on In Vitro Release Assessment: a Case Study Using Dexamethasone - Catheleeya Mekjaruskul; André O’Reilly Beringhs; Wei-Chung Luo; Qingguo Xu; Matthew Halquist; Bin Qin; Yan Wang; Xiuling Lu (AAPS PharmSciTech, 2021)

HIV-1 Tat and opioids act independently to limit antiretroviral brain concentrations and reduce blood–brain barrier integrity - Crystal R. Leibrand; Jason J. Paris; Austin M. Jones; Quamrun N. Masuda; Matthew S. Halquist; Woong-Ki Kim; Pamela E. Knapp; Angela D. M. Kashuba; Kurt F. Hauser; MaryPeace McRae (Journal of NeuroVirology, 2019)

In Vitro Aqueous Fluid-Capacity-Limited Dissolution Testing of Respirable Aerosol Drug Particles Generated from Inhaler Products - Deepika Arora; Kumar A. Shah; Matthew S. Halquist; Masahiro Sakagami (Pharmaceutical Research, 2010)